Transport Law : [selective bibliography] - Aleksandra Čar (Poredbeno Pomorsko Pravo)
This is a list of bibliographic references to selected articles, papers, books and chapters in books in the field of transport law, published in scientific and research journals and other publications by Croatian and foreign (mainly European) publishers from 2010 to 2023. Included are works published in English and Croatian and to a lesser extent in French and German. The purpose of this bibliography is to facilitate the work of researchers in the field of transport law or within one of its narrower areas such as: road transport; rail transport; insurance of transport risks; competition in the transport sector; multimodal transport; and tourism and passenger rights. Given that maritime law is the main subject of research and scientific interest of the Adriatic Institute, a separate bibliography dedicated exclusively to that branch of transport law is being prepared for the next issue of the Maritime Comparative Law Journal (to be published in 2024). OSCOLA (Oxford University Standard for the Citation of Legal Authorities) rules for citing legal sources are used throughout the bibliography.